تأثير استخدام اللعبة اللغوية "ABC 5 Dasar" على قدرة الطلاب في استيعاب المفردات العربية في الصف الثامن المتوسط بمدرسة المحمدية 16 سي رمباه - Humaira Ananda Zagi, humaira; Slamet Riyadi, Slamet; Tumanggor, Ilham (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
The purpose of this study is to determine the effect of the use of ABC 5 Dasar language games on students' ability to understand Arabic vocabulary in the eighth grade students of MTs Muhammadiyah 16 Sei. Rampah Academic Year 2023/2024. The research method used in this study is a quantitative approach of experimental methods. With a true experimental design, namely posttest only control. The data analysis technique used was parametric intangible statistical data with a t-test. The results obtained were that there was an effect of the use of the traditional game ABC 5 Dasar on students' ability to master Arabic vocabulary with an average of 77.3 posttest results in the experimental class and an average posttest result of 39.2 in the control class, with the results of the t test having a significant value of 0.00 where less than 0.05 so that Ho was rejected and Ha was accepted. In the sense that there is a significant influence in the use of the ABC 5 Dasar game on students' ability to master Arabic vocabulary in the eighth grade students of MTs Muhammadiyah 16 Sei. Rampah.